Spartina alterniflora invasion significantly alters the assembly and structure of soil bacterial communities in the Yellow River Delta - Sun, Pengyuan; Wu, Yuxin; Zhu, Pengcheng; Wang, Jingfeng; Yu, Xiaona; Guo, Weihua (Frontiers in Microbiology, 2025)
Soil microbial communities are integral to almost all terrestrial biogeochemical cycles, which are essential to coastal wetland functioning. However, how soil bacterial community assembly, composition, and structure respond to native and non-native plant invasions in coastal wetlands remains unclear. In this study of the coastal wetlands of the Yellow River Delta in China, the assembly, community composition, and diversity of soil bacterial communities associated with four wetland plant species (Phragmites australis, Spartina alterniflora, Suaeda salsa, and Tamarix chinensis) and four soil depths (0–10 cm, 10–20 cm, 20–30 cm, and 30–40 cm) were characterized using high-throughput sequencing. Plant species identity, as well as environmental factors, rather than soil depth, was found to play predominant roles in shaping the diversity and structure of wetland soil bacterial communities. S. alterniflora invasion altered bacterial community structure and increased bacterial diversity. Phragmites australis-associated bacterial communities were enriched with sulfate-reducing bacteria such as Desulfurivibrio and Desulfuromonas. In comparison, S. alterniflora-associated bacterial communities were enriched with both sulfate-reducing bacteria (SEEP-SRB1) and sulfate-oxidizing bacteria (Sulfurimonas), which maintained a dynamic balance in the local sulfur-cycle, and thereby enhanced S. alterniflora growth. In addition, stochastic processes dominated the assembly of soil bacterial communities associated with all four plant species, but were most important for the S. alterniflora community. The S. alterniflora-associated bacterial community also showed stronger interactions and more extensive connections among bacterial taxa; a co-occurrence network for this community had the greatest average clustering coefficient, average degree, modularity, and number of links and nodes, but the lowest average path length. Altogether, individual plant species had distinct effects on soil bacterial community assembly and structure, with the invasive species having the strongest impact. These results provide insights into microbial ecology and inform management strategies for coastal wetland restoration.